MENGELOLA TINGKAT LIKUIDITAS DAN RENTABILITAS PERUSAHAAN MELALUI IMPLEMENTASI EFEKTIVITAS CASH BUDGET - Miartana Putu (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
This study aimed to determine the management of liquidity and profitability of the company through the implementation of effective use of the cash budget. The design of this study used a qualitative approach with the company’s financial manager informant with the help of an open questionnaire to obtain a cash budget implementation and the documentation data in the form of the company’s financial statement. The validity test of the data used triangulation model. The results showed that managing the effective level of liquidity and profitability of the company was based on effective drafting and implementing for the cash budget of companies at first. After the cash budget was prepared, the situation of liquidity and profitability of the company became better. The limitation of this study only examined in one company and to be suggested for future researchers to look at more than one company.